South latitude and household economic control by Peruvian women - León, Federico (Pontificia Universidad Católica del Perú, 2012)
Southern women’s greater autonomy versus northern women’s more traditional submission to the husband were hypothesized in 1984 to explain variations in Peruvian women’s fertility desires. An analysis of data from Peru 2004-2008 Continuous Demographic and Family Health Survey supports this hypothesis by showing a significant north-to-south growth of women’s control upon husband’s income and, less consistently, household purchasing decisions. These relationships are not explained by variables also correlated with meridionality, such as aboriginal ethnicity, women’s material/informational power, age difference with the husband’s, or working for cash. Findings suggest new hypotheses, concerning the distribution of assertiveness and warmth in the Peruvian territory.